2022
DOI: 10.1186/s12882-022-02726-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression and 7-day time course of circulating microRNAs in septic patients treated with nephrotoxic antibiotic agents

Abstract: Background Through regulation of signaling pathways, microRNAs (miRNAs) can be involved in sepsis and associated organ dysfunction. The aims of this study were to track the 7-day time course of blood miRNAs in patients with sepsis treated with vancomycin, gentamicin, or a non-nephrotoxic antibiotic and miRNA associations with neutrophil gelatinase-associated lipokalin (NGAL), creatinine, procalcitonin, interleukin-6, and acute kidney injury (AKI) stage. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…miR-15a-5p at day 7 of gentamicin treatment provides good discrimination between AKI and non-AKI. miR-155-5p and miR-192-5p positively correlate with creatinine and neutrophil gelatinase-associated lipokalin in patients receiving vancomycin (210). These data suggest that miRNAs expression might be modulated by antimicrobials, and may serve as diagnostic markers in sepsis patients receiving nephrotoxic antibiotics.…”
Section: Other Mirnasmentioning
confidence: 74%
“…miR-15a-5p at day 7 of gentamicin treatment provides good discrimination between AKI and non-AKI. miR-155-5p and miR-192-5p positively correlate with creatinine and neutrophil gelatinase-associated lipokalin in patients receiving vancomycin (210). These data suggest that miRNAs expression might be modulated by antimicrobials, and may serve as diagnostic markers in sepsis patients receiving nephrotoxic antibiotics.…”
Section: Other Mirnasmentioning
confidence: 74%
“…Previous data indicate that miR-155-5p exerts a signi cant in uence on multiple pathways associated with sepsis and renal damage, and a direct relationship exists between the activation of miR-155-5p and increased expression of pro-in ammatory IL-6 cytokine and chemoattractant IL-8 cytokine [23,24]. Earlier studies showed that up-regulation of miR-155 has cardioprotective properties [25].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the potential value of microRNA as a diagnostic tool for septic AKI. Some -15a-5p, microR-22-3p, and microR-452 (Liu et al 2020b, Petejova et al 2022. The expression of microR-574-5p can differentiate the AKI occurrence from septic patients, indicating the predictive potential of microRNAs in the clinic (Liu et al 2021).…”
Section: Discussionmentioning
confidence: 99%